2015
DOI: 10.1088/0957-4484/27/6/065301
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of free-standing lithium niobate nanowaveguides down to 50 nm in width

Abstract: Nonlinear optical nanoscale waveguides are a compact and powerful platform for efficient wavelength conversion. The free-standing waveguide geometry opens a range of applications in microscopy for local delivery of light, where in situ wavelength conversion helps to overcome various wavelength-dependent issues, such as biological tissue damage. In this paper, we present an original patterning method for high-precision fabrication of free-standing nanoscale waveguides based on lithium niobate, a material with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Ion beam irradiation with subsequent chemical etching can be classified as a lithography technique but the development process results in the fabrication of a designed structure directly in the irradiated material without using a resist mask. It has been shown that this method can be applied to the fabrication of nanostructures from various materials, such as silicon [1][2][3], silicon dioxide [4][5][6][7][8][9][10][11][12][13][14], sapphire [15][16][17], lithium niobate [18][19][20][21] and silicon nitride [22][23][24][25]. In our work silicon dioxide was chosen due to its widespread in semiconductor industry.…”
Section: Introductionmentioning
confidence: 99%
“…Ion beam irradiation with subsequent chemical etching can be classified as a lithography technique but the development process results in the fabrication of a designed structure directly in the irradiated material without using a resist mask. It has been shown that this method can be applied to the fabrication of nanostructures from various materials, such as silicon [1][2][3], silicon dioxide [4][5][6][7][8][9][10][11][12][13][14], sapphire [15][16][17], lithium niobate [18][19][20][21] and silicon nitride [22][23][24][25]. In our work silicon dioxide was chosen due to its widespread in semiconductor industry.…”
Section: Introductionmentioning
confidence: 99%
“…25 Whereas a single adiabatic coupler only provides limited filtering, a stack of such couplers, similar to other cascaded approaches, 21,22 might be able to provide pump extinction in excess of 100 dB, which can be an interesting topic of study in the future. Furthermore, as the particular implementation using titanium indiffused waveguides in lithium niobate is not very compact, it will be important to investigate whether waveguiding structures based on high-index-contrast waveguides 21,27 allow substantial reductions of the system dimensions while retaining the adiabatic filtering properties.…”
mentioning
confidence: 99%